Q: How do you simplify -4x plus 9x equals?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

Right, 3x-4x+9x-x1. 3x - x = 2x2. 9x-4x = 5x- 2x +5x = 7x

9x = 4x + 45 5x = 45x = 9

4x+7=9x+7 -5x=0 x=0

9x + 8 = 4x + 23Subtract 8 from both sides9x = 4x + 15Subtract 4x from both sides5x = 15Divide both sides by 5x = 3

9x2+9x-12 All I can do is simplify this. I can't solve it unless turn this expression into an equation.

Related questions

Right, 3x-4x+9x-x1. 3x - x = 2x2. 9x-4x = 5x- 2x +5x = 7x

x+5+3x-7+9x+3-4x Collect like terms: 9x+1

9x = 4x + 45 5x = 45x = 9

4x+7=9x+7 -5x=0 x=0

9x + 8 = 4x + 23Subtract 8 from both sides9x = 4x + 15Subtract 4x from both sides5x = 15Divide both sides by 5x = 3

9x2+9x-12 All I can do is simplify this. I can't solve it unless turn this expression into an equation.

4x + 55 = 9x + 10 55 = 5x + 10 45 = 5x x = 9

i thinking this answer should be -20

x=9

In this case you just add them together to make 9x.

4x+3=9x-4+4 +44x+7=9x-4x -4x7=5x-------57/5=1.41.4=x

9x+3-25 = 4x-2 5x = 20 x = 4